MEMPERTIMBANGKAN CONSTITUTIONAL COMPLAINT SEBAGAI KEWENANGAN MAHKAMAH KONSTITUSI (Lex Jurnalica, 2017)
AbstractConstitutional court is a state institution was derived from reformation. The existence of Constitutional court is in the third of constitution alteration by means of article 24 C. In the article 24 C section (1), Constitutional court’s authority limitatively was defined into four categories namely: review the act towards constitution, cut off the legal action of the state institution’s authority in which it was originated from the constitution, cut off the dispersion of political parties and round out the legal action of general elections. The development of public institutions lately seems to push Constitutional court doing the expansion of authority on the Constitutional Complaint. It clearly seen from the violation of citizen’s constitutional right doing by public institution. At this time, constitutional complaint is handled by the review of act toward the constitution because there is no legal remedy of this case. Keywords: Constitutional court, constitutional complain Abstrak Mahkamah Konstitusi merupakan lembaga negara hasil reformasi. Kehadiran Mahkamah Konstitusi terjadi pada perubahan ketiga Undang-Undang Dasar Negara Republik Indonesia Tahun 1945 melalui Pasal 24C. Dalam Pasal 24C ayat (1) kewenangan Mahkamah Konstitusi secara limitatif dirumuskan yaitu: Menguji Undang-Undang terhadap Undang-Undang Dasar, Memutus sengketa kewenangan lembaga negara yang kewenangannya diberikan oleh Undang-Undang Dasar, memutus pembubaran partai politik dan penyelesaian sengketa pemilihan umum. Perkembangan ketatanegaraan belakangan ini seakan memaksa Mahkamah Konstitusi untuk memperluas kewenangannya dalam hal Constitutional Complaint atau dapat juga disebut dengan Pengaduan Konstitusional. Kebutuhan ini dapat dilihat pada banyaknya lembaga publik yang melanggar hak konstitusional warga negara melalui perbuatan lembaga publik. Namun wadah untuk pengaduan ini masih belum ada, hanya saja untuk saat ini untuk kepentingan pewadahan Constitutional Complaint dibungkus melalui pengujian undang-undang terhadap undang-undang dasar.Kata kunci: Mahkamah Konstitusi, constitutional complaint.